Absolute quantification of microRNA miR-875-5p in temporal artery biopsies and its biomarker potential for giant cell arteritis - Bolha, Luka; Smajlović, Elvisa; Hočevar, Alojzija (Frontiers in Immunology, 2026)
ObjectivesTo perform absolute quantification of miR-875-5p expression in temporal artery biopsies (TABs) of patients with giant cell arteritis (GCA), associate miR-875-5p copy number with histological and clinical characteristics of patients with GCA, and evaluate the diagnostic value of absolute copy number of miR-875-5p in GCA.MethodsThe study included formalin-fixed, paraffin-embedded TABs of 45 treatment-naïve clinically proven patients with GCA, and 19 non-GCA controls. Of the included patients with GCA, 29 had histologically positive and 16 histologically negative TABs. Expression of miR-875-5p was assessed through utilization of quantitative real-time PCR (qPCR) and absolute quantification by digital PCR (dPCR).ResultsWe determined significantly higher absolute copy number of miR-875-5p in histologically positive TABs of patients with GCA, compared to histologically negative TABs of GCA and non-GCA patients, which significantly correlated with the majority of TAB histopathological parameters and several clinical characteristics of patients with GCA. Notably, we showed a good diagnostic performance of absolute copy number of miR-875-5p in discriminating patients and controls, depending on the extent of vessel wall inflammation and remodeling in affected temporal arteries.ConclusionOur study revealed that absolute quantification of miR-875-5p expression holds the potential to serve as a supporting biomarker in assessing vessel wall inflammation and remodeling in patients with GCA. Moreover, our results indicate the applicability of absolute quantification by dPCR in detecting low-abundance miRNAs in GCA-affected arterial tissue, whose limiting amounts hinder the utilization of classical qPCR.